Evaluation of Special Endurance Exercises According To Cosmin Test of Lactic Acid and Its Relation With 800m Running Achievement - Amanh, Mohammed (Journal of Physical Education, 2018)
Evaluation of Special Endurance Exercises According To Cosmin Test of Lactic Acid and Its Relation With 800m Running Achievement The first section covered the introduction of the research and the researcher discussed the importance of lactic acid in the effectiveness of running 800 meters as well as interest in physical qualities of the game. The researcher used the descriptive method on a subject of (5) Iraqi team runners of the applicants representing the in the event ran 800 meters and was presented in this section the mechanism of work and how the variables were chosen and the method of conducting the main experiment, The researcher concluded with a set of conclusions and recommendations presented in the fifth section. The most important conclusion is that endurance exercises according to the Cosmin test followed by the 800 meter walkers need to reconsider the improvement of operations chemical in muscle cells to increase the ability of the racers to produce and carry lactic acid and continuously take into account the principle of privacy in endurance exercises, and the most important recommendations must be adopted sequential methodology when evaluating the endurance exercises for those running 800 meters.